Rosa × damascena Herrm. From Azaran region, Kashan: rich in saturated and unsaturated fatty acids with inhibitory effect against Proteus mirabilis - Mansureh Ghavam (BMC, 2024)
Abstract Background One of the most widely used medicinal plants in Iranian traditional medicine, Rosa × damascena Herrm. (mohammadi flower) that the people of Kashan use as a sedative and to treat nervous diseases and constipation. In this research, the yield, chemical composition and antimicrobial activity of the essential oil of this plant were evaluated for the first time from Azaran region, Kashan. Methods The essential oil was extracted by means of hydrodistillation (Clevenger), and its chemical compounds were identified and determined by GC/MS. The antimicrobial activity of the essential oil was determined by the diffusion method in agar, the minimum growth inhibitory concentration (MIC) and the minimum concentration capable of killing bacterial/fungal microorganisms (MBC/MFC). Results The results showed that the yield of essential oil was 0.1586 ± 0.0331% (w/w). Based on the results of the chemical composition analysis of R. x damascena essential oil, 19 different compounds (98.96%) were identified. The dominant and main components of the essential oil were oleic acid (48.08%), palmitic acid (15.44%), stearic acid (10.17%), citronellol (7.37%) and nonadecane (3.70%). Based on the results of diffusion in agar, the highest zone of inhibition against Candida albicans (ATCC 10231) was ~ 9.5 mm. The strongest inhibitory activity of R. x damascena essential oil against Gram-negative Proteus mirabilis (ATCC 43071) was with the diameter of the inhibition zone (~ 9 mm), which was equal to the strength of rifampin (~ 9 mm). Conclusion Therefore, this essential oil is a promising natural option rich in fatty acids, which can be a potential for the production of natural antimicrobials against infectious diseases, especially urinary tract infections.